VD_FINDINFO Décision / 2012 / 915 vom 31. August 2012 - VD Tribunal cantonal (2012)
ERREUR, ERREUR SUR LES FAITSDROIT PÉNAL, POLICE, VIOLENCE, CLASSEMENT DE LA PROCÉDURE | 123 CP, 13 CP, 144 CP, 186 CP, 310 CPP (CH)